Perfusion phantom: An efficient and reproducible method to simulate myocardial first‐pass perfusion measurements with cardiovascular magnetic resonance†. Issue 3 (24th April 2012) - Chiribiri, Amedeo; Schuster, Andreas; Ishida, Masaki; Hautvast, Gilion; Zarinabad, Niloufar; Morton, Geraint; Otton, James; Plein, Sven; Breeuwer, Marcel; Batchelor, Philip; Schaeffter, Tobias; Nagel, Eike
Abstract The aim of this article is to describe a novel hardware perfusion phantom that simulates myocardial first‐pass perfusion allowing comparisons between different MR techniques and validation of the results against a true gold standard. MR perfusion images were acquired at different myocardial perfusion rates and variable doses of gadolinium and cardiac output. The system proved to be sensitive to controlled variations of myocardial perfusion rate, contrast agent dose, and cardiac output. It produced distinct signal intensity curves for perfusion rates ranging from 1 to 10 mL/mL/min. Quantification of myocardial blood flow by signal deconvolution techniques provided accurate measurements of perfusion. The phantom also proved to be very reproducible between different sessions and different operators. This novel hardware perfusion phantom system allows reliable, reproducible, and efficient simulation of myocardial first‐pass MR perfusion. Direct comparison between the results of image‐based quantification and reference values of flow and myocardial perfusion will allow development and validation of accurate quantification methods. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.